Trust and Breach of the Psychological Contract - Robinson, Sandra L. (Administrative Science Quarterly, 1996)
I would like to thank Karl Aquino, Joel Brockner, Daniel Forbes, Matthew Kraatz, Judi McLean Parks, Alexandra Mithel, Lynn Shore, Jon Turner, Linn Van Dyne, Batia Wiesenfeld, Dale Zand, and four anonymous reviewers for their helpful assistance with this manuscript. This paper examines the theoretical and empirical relationships between employees' trust in their employers and their experiences of psychological contract breach by their employers, using data from a longitudinal field of 125 newly hired managers. Data were collected at three points in time over a two-and-a-half-year period: after the new hires negotiated and accepted an offer of employment; after 18 months on the job; and after 30 months on the job. Results show that the relationship between trust and psychological contract breach is strong and multifaceted. Initial trust in one's employer at time of hire was negatively related to psychological contract breach after 18 months on the job. Further, trust (along with unmet expectations) mediated the relationship between psychological contract breach and employees' subsequent contributions to the firm. Finally, initial trust in one's employer at the time of hire moderated the relationship between psychological contract breach and subsequent trust such that those with high initial trust experienced less decline in trust after a breach than did those with low initial trust.